Substrate selectivity of an isolated enoyl reductase catalytic domain from an iterative highly reducing fungal polyketide synthase reveals key components of programming. Issue 2 (30th September 2016) - Roberts, Douglas M.; Bartel, Christoph; Scott, Alan; Ivison, David; Simpson, Thomas J.; Cox, Russell J.
Abstract : The complete stereochemical course and substrate selectivity of the enoyl reductase domain from the fungal polyketide synthase squalestatin tetraketide synthase (SQTKS) have been determined. Abstract : A cis -acting enoyl reductase (ER) catalytic domain was isolated from a fungal highly reducing iterative polyketide synthase (HR-iPKS) for the first time and studied in vitro . The ER from the squalestatin tetraketide synthase forms a discrete dimeric protein in solution. The ER shows broad substrate selectivity, reducing enoyl species including both natural and unnatural substrates. Pantetheine-bound substrate thiolesters reacted much faster than the corresponding SNAC thiolesters. The unnatural substrates included Z -olefins, 2-ethyl olefins and pentaketides. Methylation of the substrate modifies the activity of the ER such that the 2, 4-dimethyl oct-2-enoyl substrate fits into the active site but cannot be reduced. A new NMR-based assay was developed for the direct observation of the stereochemical preferences at the 4′ position of the NADPH cofactor and the C-2 and C-3 positions of the substrates. The assay reveals that the fungal iPKS ER-catalysed reaction is stereochemically identical to that of the vertebrate FAS (vFAS) at the cofactor 4′ position and the substrate 3-position, but the high stereoselectivity displayed by intact SQTKS is lost such that reprotonation at the 2-position is unselective by the isolated ER. A 3D model of ER was consistent with these observations and showed that the ER may sequester its final substrate to prevent further chain extension. The results support a developing model for programming by HR-iPKS in which competition for substrates between restrictive and permissive catalytic domains chaperones the growing polyketide to completion, while allowing for errors and evolution.